Spatial openness and student activities in an atrium: A parametric evaluation of a social informal learning environment. (September 2020) - Wu, Xianfeng; Oldfield, Philip; Heath, Tim
Abstract: The use of atria for students' informal learning activities is becoming a common architectural design strategy in contemporary higher education buildings, especially in dense urban settings. However, while researchers have focused on the relationship between students' perception, preferences and behaviours in social learning spaces, the spatial attributes themselves tend to be neglected in the literature. By exploiting digital spatial analysis tools, this paper uses the parameters of 'viewing volume' and 'viewing area' to compare the spatial openness of different spaces within an atrium in a higher education institution. Timeframe capture and interviews are also employed to record the distribution of student activities. The spatial attributes of the atrium and the distribution of student activities are analysed to explore links between the two. The results indicate that the viewing volume in the two-storey-height space is the highest, while viewing area in the staircase space is the highest. These spaces tended to coincide with higher frequencies of 'see and be seen' activities, such as students waiting and looking around (71.54% and 56.32% respectively). The standard deviations of the mean viewing volume and viewing area are the greatest in the three-storey space, suggesting a diversity of spatial openness. This coincided with the highest frequency of activities that require social interactions, such as gathering and group study (92.40% and 58.10% respectively). These findings suggest that spatial openness can impact student activities in an educational setting, and an atrium specifically. These novel methods also open new horizons for interpreting spatial structure in architecture. Highlights: A parametric methodology is used to quantify spatial openness in an atrium . Student activities in the atrium are observed by timeframe capture and interviews. Activities that need visibility are more frequent in greater spatial openness. Gathering and discussing activities are more frequent in varied spatial openness.